2018
DOI: 10.1080/0284186x.2018.1438658
|View full text |Cite
|
Sign up to set email alerts
|

Anal sphincter dysfunction in patients treated with primary radiotherapy for anal cancer: a study with the functional lumen imaging probe

Abstract: Patients treated with radiotherapy or chemoradiation for anal cancer have low anal resting and squeeze pressures as well as reduced resistance to distension and flow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 46 publications
1
25
0
1
Order By: Relevance
“…Regardless of the endpoints used, significantly higher anal distensibility was found in patients with fecal incontinence than in HV in all clinical studies , 93,96,99,102,104 . This has been demonstrated in patients with poor internal anal sphincter function resulting from systemic sclerosis, 104 in patients treated with sphincter‐sparing radiotherapy or chemoradiation for anal cancer 96 and whatever the cause of fecal incontinence 99,100 . It has been suggested that FLIP assessment would be a more selective tool to discriminate between patients with fecal incontinence and HV 99 but not confirmed by others 106 .…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Regardless of the endpoints used, significantly higher anal distensibility was found in patients with fecal incontinence than in HV in all clinical studies , 93,96,99,102,104 . This has been demonstrated in patients with poor internal anal sphincter function resulting from systemic sclerosis, 104 in patients treated with sphincter‐sparing radiotherapy or chemoradiation for anal cancer 96 and whatever the cause of fecal incontinence 99,100 . It has been suggested that FLIP assessment would be a more selective tool to discriminate between patients with fecal incontinence and HV 99 but not confirmed by others 106 .…”
Section: Resultsmentioning
confidence: 89%
“…While the methodology used was quite similar among all studies, there is until now, no consensus about the best parameters to record with FLIP technology. Several parameters have been suggested from the most complexes (anal canal stiffness defined on the basis of the pressure and diameter changes when the volume increased from 1 to 50 mL, 93‐95 flow resistance of the anal canal defined from the anal canal length, the middle part diameter of the anal canal and the dynamic viscosity of the inflated bag 96 or mechanical work of the anal sphincter muscle, 97 to the most simple (wall tension (T = P.r), 98 anal DI (CSA/P), 99,100 anal compliance (D/P), 97 yield pressure when the most resistant (middle) part of the sphincter begins to distend 93‐95 . More recently, Zifan et al described the use of area‐pressure and area‐tension‐loop analysis of the anal sphincters and puborectalis muscles in normal subjects and fecal incontinent patients, assessing the relationship between changes in muscle length (secondary to anal distension) and muscle function 101,102 .…”
Section: Resultsmentioning
confidence: 99%
“…Other authors also identified neoadjuvant radiotherapy as a factor leading to LARS [ 26 , 42 , 43 ]. Postoperative radiotherapy also causes deterioration of anal sphincter function [ 44 , 45 ]. The effect of radiotherapy is not only clinically significant, but also is visible in manometric studies [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…It revealed a trend; IAS elasticity had a moderate inverse correlation with MRP of anorectal manometric data, regardless of whether measurements were made before or after CRT. We speculate that CRT may have induced sclerosis of the IAS and consequently an increase in MRP in the short term, such as 1 month after the completion of CRT; however, several studies demonstrated that CRT decreased MRP in the long term, such as 1 year after surgery 27,28 . Further accumulation of the cases is needed to identify changes caused by CRT in IAS elasticity.…”
Section: Discussionmentioning
confidence: 95%